Acknowledgement to Reviewers of Marine Drugs in 2016 - Marine Drugs Editorial Office (Marine Drugs, 2017)
The editors of Marine Drugs would like to express their sincere gratitude to the following reviewers for assessing manuscripts in 2016. [...]